Contraception use and pregnancy in women receiving a 2-dose Ebola vaccine in Rwanda: A retrospective analysis of UMURINZI vaccination campaign data. - Rosine Ingabire; Julien Nyombayire; Amelia Mazzei; Jean-Baptiste Mazarati; Jozef Noben; Michael Katwere; Rachel Parker; Sabin Nsanzimana; Kristin M Wall; Tyronza Sharkey; Felix Sayinzoga; Amanda Tichacek; et al. (PLoS Medicine)
Background Rwandan individuals bordering the Democratic Republic of the Congo (DRC) are at-risk of Ebola virus disease. A 2019 to 2021 vaccination campaign called UMURINZI offered a Janssen Vaccines & Prevention B.V. 2-dose heterologous Ebola vaccine regimen (Ad26.ZEBOV, MVA-BN-Filo) to Rwandan individuals aged ≥2 years and not pregnant. In this region with high rates of pregnancy, preventing pregnancy until their second dose of the Ebola vaccine is essential to ensure full protection. This analysis describes contraceptive use, pregnancy incidence, serious adverse events (SAE), and the effect of pregnancy and SAE on receipt of the second dose among women in the UMURINZI vaccination campaign. Methods and findings During the vaccination campaign, women who were fertile and sexually active were counseled as part of the campaign by trained UMURINZI nursing staff about preventing pregnancy until dose two (56 days post-dose one) and offered contraception. Women were followed up to their second dose appointment. Contraception, pregnancy incidence, and SAE were recorded. Of the 47,585 fertile and sexually active women, the mean age was 28·0 years (standard deviation 9·9 years), 54·7% (n = 26,051) were from Rubavu and 45·3% (n = 21,534) were from Rusizi, and 71·9% (n = 34,158) had not crossed the DRC border in the last year. Sixty-six percent (66·6%, n = 31,675) were not using modern contraception at baseline and 19·1% (n = 9,082) were using hormonal implants, 10·9% (n = 5,204) injectables, 2·9% (n = 1,393) oral contraceptive pills (OCPs), and 0·5% (n = 231) intrauterine devices. After contraceptive counseling, 8·0% (n = 2,549) of non-users initiated a method of contraception and 3·6% (n = 50) of OCP users switched to a more effective method. Of the 969 incident pregnancies detected after dose one, 18·8% (n = 182) resulted in an obstetric SAE, primarily due to spontaneous abortion which occurred in 16·0% (n = 155) of all incident pregnancies. Other obstetric SAE included 14 blighted ova, 9 stillbirths, 1 termination due to hydrops fetalis, 1 cleft palate, and 2 threatened abortions resulting in normal deliveries. Six pregnant women had a non-obstetric SAE (0·6%), including 1 postpartum death from COVID-19 and 5 hospitalizations. Among the 74,002 women without an incident pregnancy detected after dose one, 0·01% (n = 4) had an SAE; 2 were fatalities due to hypertension and diabetes in one case and seizures in the other, and the other 2 were hospitalizations. No SAE were determined to be related to the vaccine by the program physicians. Among the 74,002 women without an incident pregnancy detected after dose one, 94·6% (n = 69,986) received dose two; in contrast, among the 969 women with an incident pregnancy detected after dose one, 34·5% (n = 334) received dose two after pregnancy completion. Conclusions Many fertile and sexually active women who sought vaccination during UMURINZI were not using contraception prior to vaccination, and contraceptive method uptake after family planning counseling and method provision was low. Most women who became pregnant after the first vaccination dose did not receive the second dose, thus potentially reducing protection against Ebola. Family planning messaging for this context should be developed and pilot-tested. The estimated risk of spontaneous abortion was similar to previous estimates from Rwanda and other African countries.